2007
DOI: 10.21273/hortsci.42.7.1670
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Plant Regeneration from Leaf Tissues of Buddleia Species

Abstract: The effects of genotype, basal medium, plant growth regulator (PGR), dark treatment, and antibiotics on shoot regeneration of two Buddleia cultivars, B. davidii 'Potters Purple' and Buddleia 'Lochinch', were investigated. In vitro shoots were regenerated from leaf tissues in either Murashige and Skoog (MS) or woody plant medium (WPM) media supplemented with benzyladenine (BA). In general, more shoots were regenerated in WPM medium than in MS medium. Dark treatment for 3 to 5 weeks dramatically increased shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In more recent research caulogenesis was facilitated by CARB when the shoots were regenerated indirectly from callus (Suzuki et al 1998;Bhau and Wakhlu 2001;Tang et al 2004). Positive results have also been reported for direct regeneration protocols when an initial dark culture period, that would be expected to stimulate callusing prior to the onset of shoot differentiation, was included (Billings et al 1997;Hammerschlag et al 1997;Dai and Castillo 2007).…”
Section: Shoot Morphogenesismentioning
confidence: 93%
“…In more recent research caulogenesis was facilitated by CARB when the shoots were regenerated indirectly from callus (Suzuki et al 1998;Bhau and Wakhlu 2001;Tang et al 2004). Positive results have also been reported for direct regeneration protocols when an initial dark culture period, that would be expected to stimulate callusing prior to the onset of shoot differentiation, was included (Billings et al 1997;Hammerschlag et al 1997;Dai and Castillo 2007).…”
Section: Shoot Morphogenesismentioning
confidence: 93%
“…The experimental data has been fitted into Monod equations. [4] , Organic ingredients are take in B5 [5] .Culture media used in this study were supplemented with 3% sucrose and 0.7% agar [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Limited and controversial information is available regarding the effect of dark treatment on plant regeneration. It has been reported that dark treatment significantly increased plant regeneration (Gu and Zhang 2005;Ahn et al 2007;Dai and Castillo 2007); while other research has shown no positive effect of dark treatment on plant regeneration (Sarma and Rogers 1998). Little is known about why dark treatment influences in vitro regeneration.…”
Section: Discussionmentioning
confidence: 98%